Proxy wars : suppressing violence through local agents - Berman, Eli; Lake, David A., 1956-; Macdonald, Julia (Cornell University Press, 2019)
"Analytical narratives examine when and where major powers can work through local proxies rather than commit their own troops. Cases include Denmark under Nazi occupation, the Korean War, El Salvador, Colombia, and present-day Iraq, Yemen, and Afghanistan. Most focus on the United States, but Israel's relations with Lebanon and Gaza and the Palestinian Authority are also featured"--